Late effects of cycle competition on arterial stiffness. A preliminary study - Colin, E.; Arbez, L.; Mourot, L.; Laurant, P.; Tordi, N. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The purpose of this study was to examine the effects of a cycle competition on the large arteries stiffness, 24-hours after the end of the effort. Methods: Two males elite cyclists were studied before and after performing a stage-race. Their heart rate (HR) was measured continuously during the two competition days. The impact of the competition on their vascular system was determined using the measure of pulse wave velocity (PWV), an index of regional arterial stiffness. HR and blood pressure were also measured before and 24-hours postexercise. Results: During the race, mean cyclists HR were relatively similar. Changes in PWV and HR were found after competition: these measures increased for the offensive subject and decreased for the other. Conclusion: Despite their involvement in the same cycling competition, we suggest that the long-term effects induced by effort on arterial stiffness were inverted according to the subject's comportment during the race. This study should be completed by others measures in order to precise our results and to precise the possible link between arteries stiffness and the recovery kinetic process, both depending on the cardiovascular autonomic nervous system control.